MODEL IKHTIAR PEMBUDAYAAN NILAI-NILAI PANCASILA DI KALANGAN MASYARAKAT DESA - Masrukhi Masrukhi; Margi Wahono (Bhineka Tunggal Ika: Kajian Teori dan Praktik Pendidikan PKn, 2019)
Rural communities are vulnerable to the effects of globalization. Their limited access to information from outside their communities often results in shock, because of the order in their circles. In turn, understanding, appreciation, and implementation of Pancasila in their daily lives can gradually erode. Many of their behaviors no longer conform to Pancasila values. If this happens protracted, without any efforts to strengthen the values of the Pancasila, there will inevitably be a natural silting of ideology in their daily lives. Therefore, it is necessary to identify the existing social capital among rural communities. To then identify the existing social capital in rural communities, to be revitalized to strengthen the implementation of the value of Pancasila among them. Pancasila Clinic among rural communities is considered to have a high effectiveness in the effort to strengthen the culture of Pancasila values.